REBUSAN LOBAK (RAPHANUS SATIVUS L) TERHADAP PLAK GIGI - Irmanita Wiradona; Bambang Sutomo; Prasko Prasko (Jurnal Kesehatan Gigi, 2017)
TITLELobak stew (Raphanus sativus L) to dental plaqueABSTRACTStreptococcus mutans, Lactobacillus spp. and Candida albicans are the dominant microorganisms found in dental plaque, acidogenic and acidophilic in nature and have the ability to convert carbohydrate to acid. Plaque control is an effort to remove and prevent plaque buildup on tooth surfaces that can be done mechanically or chemically. Radish extract can inhibit the growth of Streptococcus mutans in biofilm formation in vitro. The purpose of this study is to determine the effect of stewed water rinse of radish (Raphanus sativus L) to the formation of dental plaque.This study is a quasi-experimental research with Pre-and Post-test Group design. The sample in this study is the students of grade V and VI SDN Kadirejo 03 Semarang regency, amounting to 34 students. The samples were divided into two groups, the first group was given 50% concentration of stewed waterof radish and the second group was given 100% concentration of stewed waterof radish each for 30 seconds followed by index plaque measurement by PHP (Personal Hygiene Performance) method. The data obtained were analyzed using statistical Independent t-test.The results showed that 100% concentration of stewed waterof radish can decrease the index plaque by 0.34 while 50% concentration of stewed waterof radish can decrease the index plaque by 0.28. But statistics show no difference of stewed water rinse of radish of 100% concentration and 50% concentration. From the research results can be recommended to conduct research by material extraction methods that do not damage the active substance of the material. Keywords : Stewed of radish (Raphanus sativus L), dental plaque